Dependence of the isotopic composition of different precipitation types on air temperature in Central Antarctica - N. A. Tebenkova; A. A. Ekaykin; T. Laepple; D. Notz; A. V., Kozachek; A. N. Veres; Н. А. Тебенькова; А. А. Екайкин; Т. Лэппле; Д. Нотц; А. В. Козачек; А. Н. Верес (Arctic and Antarctic Research, 2021)
Water isotopes are key proxies to reconstruct past climatic conditions on our planet based on Antarctic ice core data. The accuracy of climate reconstructions depends on understanding the whole range of the processes involved in the formation of precipitation isotopic composition. The isotopic composition of precipitation in Central Antarctica has been studied in a number of works, but the difference between the isotopic composition of different types of precipitation has not yet been fully described.There are three main type of precipitation in Central Antarctica: snow, ice needles and hoar. The aim of this work is to establish the dependence of isotopic composition of different precipitation types on temperature. Precipitation samples were collected at Vostok station in Central Antarctica from 1998 to 2020 and further analyzed for δ18O and δD. For each precipitation event we have meteorological data, averaged over the time of precipitation fallout. Mean values of δD for each precipitation type were defined as follows: –444±6.5 ‰ for diamond dust, –480± 6 ‰ for hoar and –95±11 ‰ for snow. The seasonal variability of the temperature dependence of the isotopic composition was studied using the example of ice needles. According to our data, the dependence is insignificant in winter, but this needs to be confirmed by an extended dataset. The largest slope of the isotope-temperature dependence regression line is observed for the summer period and is equal to 5.34±3.11 ‰·°С–1, the autumn season has a slope of 2.1±1.3 ‰·°С–1, while for the spring period we do not have enough data for analysis. There is an insignificant difference in the slopes of the isotope-temperature dependence for different types of precipitation: 2.93±0.51 ‰·°С–1 for ice needles, 2.32±1.34 ‰·°С–1 for snow and 2.52±0.35 ‰·°С–1 for hoar. We studied the effect of blizzards on the isotopic composition of samples and concluded that one should avoid using data collected during a blizzard to study the differences in the formation of the isotopic signal ...